Comparison of the Luminex NxTAG respiratory pathogen panel and a multiplex in‐house real‐time PCR panel for the detection of respiratory viruses in symptomatic patients. Issue 9 (September 2017) - Sails, Andrew David; Eltringham, Gary; Valappil, Manoj; Waugh, Sheila; Saunders, David
Abstract : Purpose. : To evaluate the Luminex NxTAG respiratory pathogen panel (NxTAG RPP) for the detection of respiratory viruses in clinical samples from patients with the symptoms of respiratory infection. Methodology. : The NxTAG RPP was compared to an in‐house multiplex real‐time PCR panel (LDT) for the detection of respiratory viruses in 314 clinical samples from patients with the symptoms of respiratory infection. Results. : Thirty‐one samples were negative in both tests and 193 samples contained a single virus that was detected in both tests. Polymicrobial infections were detected in 74 samples, with 268 samples overall having concordant results in both assays, and there were a total of 51 discordant results in 44 samples. Two samples were invalid in the NxTAG RPP assay and were excluded from the final analysis. The overall agreement between the NxTAG RPP and LDT was very high, as indicated by the Kappa coefficients, which ranged from 0.85 for metapneumovirus up to 0.96 for RSV A, and the overall percentage agreement values of 96.2% for enterovirus/rhinovirus and 100% for influenza A, influenza B, PIV 4 and RSV B. Conclusion. : The NxTAG RPP is a sensitive and specific test for the detection of respiratory viruses and the high sample throughput and low hands‐on time make the NxTAG RPP assay suitable for screening clinical samples for respiratory pathogens.